The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1001/jamanetworkopen.2021.22255
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Allergic Reactions After Pfizer-BioNTech COVID-19 Vaccination Among Adults With High Allergy Risk

Abstract: IMPORTANCE Allergic reactions among some individuals who received the Pfizer-BioNTech (BNT162b2) COVID-19 vaccine discourage patients with allergic conditions from receiving this vaccine and physicians from recommending the vaccine.OBJECTIVE To describe the assessment and immunization of highly allergic individuals with the BNT162b2 vaccine. DESIGN, SETTING, AND PARTICIPANTSIn a prospective cohort study from December 27, 2020, to February 22, 2021, 8102 patients with allergies who applied to the COVID 19 vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
87
4
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(110 citation statements)
references
References 20 publications
7
87
4
3
Order By: Relevance
“…However, none of them developed life-threatening anaphylaxis. A recent research in JAMA network states that even highly allergic individuals can take Pfizer vaccine; however vaccination should be strictly under medical supervision and requires special precautions [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, none of them developed life-threatening anaphylaxis. A recent research in JAMA network states that even highly allergic individuals can take Pfizer vaccine; however vaccination should be strictly under medical supervision and requires special precautions [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 28 However, a recent study of 429 highly allergic individuals who received the Pfizer-BioNTech vaccine under medical observation identified a much higher rate of minor allergic reactions (1.4%) and anaphylaxis (0.7%). 29 Past vaccine reactions have largely been attributed to excipients rather than to vaccine active ingredients. 13 , 30 The cohort in the present study included 217 employees with a history of a severe allergic reaction to an injectable medication or a vaccine and 9 employees with a history of severe allergic reaction to PEG.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increase in reactogenic symptoms, including injection-site reactions, myalgia, headache, fever, fatigue, and in some cases, a transient rash. As seen in local postvaccine patients, mucocutaneous manifestations were largely mild and self-limiting, and did not correlate with the reproducibility nor severity of symptoms following next dose of vaccination [ 9 10 ]. In fact, proceeding with a second dose has been shown to be safe even in more severe reactions and cases of anaphylaxis [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Precautions for vaccine-naïve individuals have been reviewed and updated by multiple healthcare authorities around the world, as emerging evidence shows a lack of association between allergic conditions with risk of developing vaccine-associated allergic reactions [ 10 ]. Our local study similarly found that a history of anaphylaxis, multiple food allergies, and drug allergies were not associated with higher risk of vaccine-associated allergies.…”
Section: Discussionmentioning
confidence: 99%